In silico MLST for Aspergillus species identification and CYP51 gene characterization (2022)
ABSTRACT: Aspergillus spp. is an environmental fungi that can causes from localized infectious and allergic forms, to severe invasive disseases1; these clinical entities are a major health problem, with a rapidly evolving epidemiology and new groups of patients at risk2. A. fumigatus is the major etiologic agent of aspergillosis, but a few other Aspergillus species such as A. niger, A. flavus and A. terreus can also cause infections3. While most of these pathogens are phenotypically distinguished to section level, there is not enough resolution power to identify the species between the same section as they share near identical morphological characteristics4. For that reason, genomic identification of Aspergillus species is an alternative with better resolution power; and it provides additional information about biological, virulence and drugs resistance characteristics. The objective was to identify Aspergillus species through MLST and characterize the CYP51 gene